KARAKTERISTIK DEMOGRAFI DAN KLINIKOPATOLOGI PASIEN KANKER KOLOREKTAL USIA DI BAWAH ATAU SAMA DENGAN 40 TAHUN - , SANINDITA KUSUMASTUTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Backgorund: Colorectal cancer has shown remarkable incidence in Indonesia, while incidence in young patients have been observed and increased in the last two decades. Diagnosis in young patients usually comes late or has a more advanced stadium thus giving a poor prognosis as well. Aim: To obtain demographical and clinicopathological characteristic as well as therapy given to colorectal cancer patients aged 40 years old and younger. Methods: A descriptive analytical retrospective research was conducted. Medical records of colorectal patients aged 40 years old and younger, that were registered in Tulip Cancer Center of Sardjito District Hospital Yogyakarta from 2007-2011, were collected and transformed to a case report form (CRF) before sampling was taken place. Data collected included demographical and clinicopathological characteristic, and therapy received by patients. All data that fulfilled research criteria were analyzed by using SPSS statistical program to shown frequency, distribution, and significance level of each. Missing data were not analyzed. Result: From 330 colorectal patients in Tulip Sardjito, 17,6% (58/330) were aged 40 years old and younger. 65,5% patients were male with ratio between male and female 1,9:1. About 70% patients were referred from a specialist and 50% were early diagnosed with colonoscopy. The most frequent symptoms were rectal bleeding. About 53,5% were located in rectum and 76,1% cancer were adenocarcinoma, 8,7% were mucinous adenocarcinoma, and 15,2% were signet-ring cell carcinoma. Late staging (III and IV) was found in 74,2% patients and 56,25% were well-differentiated tumor. Diabetes mellitus (17,65%) and hypertension (17,65%) were the most comorbids found in young patients. Performance status in young patients was ECOGâs 1 (41,67%) or 2 (58,33%). About 20,6% patients had synchronous tumor when firstly diagnosed. Mean initial CEA level in young patients was 91,42 ng/ml. 34,7% patients received both combination of surgery and chemotherapy, with adjuvant (41,03%), locally advanced (41,03%), and metastatic (17,94%) as the first line chemotherapy setting. From 22,41% patients that were analyzed, 69,23% were having progressive disease. Conclusion: Colorectal cancer patients aged 40 years old and younger were mostly male with rectal bleeding. Most of the cancer was well-differentiated adenocarcinoma in rectum with late staging. Patients were mostly treated with combination of surgery and chemotherapy and most of the patients which could be analyzed were having progressive disease.